Performance of women dairy self-help groups in Rajasthan: a multistage principal component analysis approach - Ritu Rathore; Ravinder Malhotra; Anil Kumar Chauhan; Rajendra Jangid (Agricultural Economics Research Review, 2023)
This study evaluates the performance of 80 dairy self-help groups (SHG) run by women in the Baran and Jhalawar districts Rajasthan based on secondary data since inception to 2018. We use as indicators their institutional, savings, loaning, repayment, and income-generating performance. We used multistage principal component analysis to construct an index for each of the indicators and then a composite performance index. The performance of most SHGs was average. The empirical evidence suggests that training programmes should be organized at the village and the channelization of money by group members should be monitored continually.